SIGNS OF THE OBJECTIVE IN THE DYNAMICS OF MODERN CRIME IN RUSSIAN FEDERATION (Russian Journal of Economics and Law, 2009)
The article views the interconnection between economic development and crime change. The dynamics of registered crime on the territory of the Russian Federation is shown, the rules of its rises and falls are defined.